BERKEMBANG.ID: A Digital Technology Innovation to Enhance MSME Capacity in Supporting Digital Economic Growth in Depok City - Hadi Wijaya; Rachmawati, Dwi; Suprihadi, Untung; Desi Hertin, Revita (DINASTI RESEARCH, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the main drivers of Indonesia's economic growth, but many face challenges in adopting digital technology. This study aims to develop and evaluate the impact of the BERKEMBANG.ID digital platform in enhancing the capacity of MSMEs in Depok City, in line with achieving Sustainable Development Goal (SDG) 8. Using a mixed-methods approach, the study involves 100 MSMEs with a focus on three main indicators: digital knowledge (human resources), operational efficiency, and sales performance. The results show a significant improvement in MSMEs' capacity after using the BERKEMBANG.ID platform. Digital literacy among MSMEs increased from 40% to 75%, operational efficiency rose from 45% to 80%, and sales performance increased from 50% to 85%. These improvements were supported by the platform’s features, such as digital training modules, analytical dashboards, and marketing tools, which effectively addressed key challenges faced by MSMEs, including limited digital skills and market access. This study highlights the transformative role of digital platforms in empowering MSMEs and the importance of tailored digital solutions to meet their specific needs. By enhancing digital technology adoption, BERKEMBANG.ID not only improves MSME performance but also supports inclusive and sustainable economic growth. Future research could focus on replicating this platform in other regions and integrating advanced analytics to optimize its impact.